Visual impairment in rural and migrant Chinese school-going children: prevalence, severity, correction and associations. Issue 2 (30th October 2020) - Ma, Yue; Zhang, Xinwu; He, Fei; Ma, Xiaochen; Yi, Hongmei; Rose, Nathan; Medina, Alexis; Rozelle, Scott; Congdon, Nathan
Abstract : Purpose: To describe changes in the prevalence of visual impairment and glasses ownership with age and as associated with income and population density for visual impairment among rural and urban migrant Chinese students. Design: Meta-analysis of 12 cross-sectional, school-based studies conducted between 2012 and 2017. Setting: Rural and urban migrant schools in seven Chinese provinces. Participants: A total of 83 273 rural and urban migrant Chinese students aged 6–17 years. Results: Prevalence of visual impairment (uncorrected visual acuity ≤6/12 in either eye) rose from 19.0% at age 6 to 66.9% at 17, with the overall age-adjusted prevalence higher for girls (35.8%) than for boys (30.1%, p<0.001). The rate of glasses ownership among students who needed them increased from 13.0% at age 6 to 63.9% (p<0.001) at 17 and was significantly higher for girls (37.0%) than boys (34.7%, p<0.001). The unmet need for glasses as a proportion of the student population peaked in junior high school (31.8%). A 1% increase in per capita gross domestic product was associated with a 4.45% rise in uncorrected visual acuity (R 2 =0.057, p=0.020). Population density was significantly associated with glasses ownership among children (R 2 =0.359, p=0.012). A 1% population density increase was associated with an increase in the glasses ownership rate of 6.83%. Conclusion: Efforts are needed to improve vision screening coverage in China's schools, particularly junior high schools, as this is when many rural children leave school and glasses coverage is lowest.